Tinnitus as central noise revealed by increased loudness at thresholds - Zeng, Fan-Gang; Turner, Katie E. (Frontiers in Audiology and Otology, 2023)
Tinnitus is an auditory sensation in the absence of external sounds; its neural mechanisms remain unclear. An active loudness model suggests that tinnitus is a result of increased central noise while hyperacusis is that of increased central gain. To the extent that loudness reflects the system-level neural activities, this active model predicts that tinnitus increases loudness at thresholds but does not increase the slope of loudness function. To test this prediction, the present study compared loudness growth of various stimuli between tinnitus and non-tinnitus subjects. The stimuli were tested at frequencies without hearing loss and both tinnitus and non-tinnitus subjects had unremarkable hyperacusis. Consistent with the prediction, the loudness at threshold in tinnitus subjects were 2.3 times greater than that in non-tinnitus subjects; there was no significant difference in the slope of loudness growth between these two groups of subjects. The present result shows that traditional psychophysics, originally developed to investigate relationships between subjective sensation and physical stimulation, can also help delineate neural mechanisms underlying tinnitus and other disorders.